Criteria for Measuring Perceived Usefulness of Mobile Commerce Services - Wong, Ha Ding (2009)
The objective of this study is to identify the important criteria for measuring perceived usefulness of m-commerce services. This study was conducted in UUM as a case study. Descriptive analysis, crobanch’s alpha, pearson correlation and linear regression were used for data analysis. The results showed that privacy, efficiency, cost, convenience and trust are significantly correlated to the perceived usefulness of m-commerce services. However, security did not show significant correlation to perceived usefulness.